Quality Assessment of Clinical Practice Guidelines for the Management and Surgical Treatment of Female Stress Urinary Incontinence - Mario Vásquez-Peralta; Alison Simancas-Racines; Juan Marcos Parise-Vasco; Camila Montesinos-Guevara; Daniel Simancas-Racines (International Journal of Clinical Practice)
Clinical practice guidelines (CPGs) are tools developed to support evidence-based decision making in healthcare. However, despite the availability of CPGs for the surgical management of female stress urinary incontinence (FSUI), their methodological quality has not been evaluated. The aim of this study was to assess the methodological quality of published guidelines for the surgical management of FSUI using the AGREE II tool. A systematic search of CPGs published between 2017 and 2023 was performed in databases including MEDLINE/PubMed, LILACS, Scopus, and Trip Medical Database. Data extraction and guideline selection were performed independently by two reviewers, as was the assessment using the AGREE II instrument. Of 1459 initial records, six guidelines met the eligibility criteria. The scores for each domain evaluated were as follows: scope and purpose (45.83%; SD: 22.69), stakeholder participation (30.56%; SD: 29.03), development (48.56%; SD: 30.42), presentation clarity (58.80%; SD: 22.25), applicability (24.04%; SD: 26.36), and editorial independence (44.87%; SD: 32.88). One of the six included CPGs was rated as high quality and recommended for clinical practice. Three CPGs with modifications were recommended because there were still areas that needed improvement to enhance their quality, and two CPGs were not recommended for clinical practice because the six domains evaluated scored below 60%. According to these findings, it is essential that new CPGs developed for the surgical management of FSUI adhere to greater methodological rigor to ensure that recommendations are based on the best available evidence. Furthermore, guidelines should take into account patient values and clinical expertise to improve and facilitate effective healthcare decision making.